Tahapan dan Bentuk Partisipasi Petani Dalam Pemberdayaan Oleh Komunitas Metode Hayati Indonesia (MHI) di Desa Andongsari Kecamatan Ambulu Kabupaten Jember - Hudaifa, Ahmad; Puspanigrum, Diah (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2023)
The current agricultural development approach emphasizes the community empowerment approach. Empowerment of farmers by the MHI community in Andongsari Village, Ambulu District, Jember Regency is not easy because all of farmers are not active in every stage of empowerment activities. The method of determining the research area is carried out by a purposive method with several considerations. The research method used is qualitative research with a case study approach. Determination of informants is done by purposive sampling method. Data collection techniques through interviews, observation and documentation. The data analysis used is an interactive model of Miles and Huberman's data analysis. The validity of the data used is source triangulation. The results showed that: 1. The stages of farmer participation in the development of Biological Control Agents in Andongsari Village are (a) participation in decision making by understanding the program, being involved in operational planning and scheduling, and determining implementers and coordinators. (b) participation in the implementation phase through resource contribution and coordination. (c) participation in profit sharing, including material benefits, social benefits and personal benefits. (d) participation in the evaluation; 2. The forms of participation provided by farmers in APH development activities are (a) participation in the form of ideas (b) participation in the form of labor (c) participation in the form of property (d) participation in the form of skills and (e) participation in the form of social.